Do sagrado ao profano: uma leitura dos espaços de A volta ao lar, de Harold Pinter - Júlio Lopes Cruz; Gilberto Freire de Santana; Antônio Coutinho Soares Filho (Revista Odisséia, 2025)
This article is an analysis of the play The Homecoming, by English playwright Harold Pinter. In this sense, the work aims to address issues relating to the profane and the sacred from the environments exposed in the drama, as well as to present possible characteristics of the Theatre of the Absurd in Pinter's work, articulating diverse dialogues with other elements, such as transgression and the figure of the feminine. The study is based on the theoretical contributions of Bachelard (1998), Coutinho (2015), Cunha (2004), Eliade (2018), Enoque; Borges; Borges (2016), Esslin (2018), Marinho (2016), Mielietinski (1987), Nora (2012), Oliveira (2001) and Santos (2017). To this end, qualitative bibliographical research forms the methodological basis of the article. Thus, this work seeks to make a significant contribution to literary studies, especially those that refer to the dramatic text. Among lyrics that transgress, Harold Pinter challenges and overcomes imposed standards.